Invasive papillary breast carcinoma. Case presentation - Javier Martínez Navarro; Martha Yudey Rodríguez Pino; Virgen Yasmín Martínez Navarro; Lisanka Fumero Roldán (Medisur)
Primary invasive breast papillary carcinomas are rare, accounting for approximately 1% of all malignant tumors in that organ and are characterized by occurring in postmenopausal women aged 64 to 67 years on average. We present the case of an 84 year old woman with a breast nodule whose biopsy revealed an invasive papillary carcinoma; In spite of not manifesting telorrhea and nor its location was the habitual one. It is considered a relevant case and of interest for health professionals since this uncommon mammary neoplasm is in our country and few cases have been published.